The decline of ungulate populations in Iranian protected areas calls for urgent action against poaching. Issue 1 (12th April 2017) - Ghoddousi, Arash; Soofi, Mahmood; Hamidi, Amirhossein Kh.; Ashayeri, Sheyda; Egli, Lukas; Ghoddousi, Siavash; Speicher, Julian; Khorozyan, Igor; Kiabi, Bahram H.; Waltert, Matthias
Abstract: Poaching is cryptically but rapidly driving many species towards extinction. Knowledge of population trends of exploited species and incentives for poaching is necessary to inform appropriate conservation measures. We estimated the abundance of four ungulate species in Golestan National Park, Iran, the country's oldest protected area, where poaching of ungulates is widespread. We used line transect surveys (186 km), camera trapping (2, 777 camera-nights), point counts (64 scans) and dung counts (along 38 km), and compared population estimates with those from earlier records. We also investigated the incentives for poaching, using a semi-structured interview survey. Population estimates for 2011–2014 indicated a 66–89% decline in three ungulate species (bezoar goat Capra aegagrus, red deer Cervus elaphus and urial Ovis vignei ) compared to 1970–1978. Only wild boar Sus scrofa showed a population increase (of 58%) during the same period, possibly facilitated by religious restrictions regarding the consumption of this species. The incentives for poaching were categorized (in a non-ordinal manner) as subsistence, pleasure, tradition, trade of wild meat, and conflict with conservation regulations and bodies. The decline in hunted ungulates in this Park appears to be the result of rampant poaching, and a similar trend is evident in other protected areas in the country. We suggest the adoption of participatory conservation strategies, improvement of law enforcement practices and cooperation with international experts to reduce poaching in these protected areas. Taking into account the incentives for poaching, a combination of economic and non-economic strategies should be considered.